APENDISITIS PADA PASIEN ANAK: BUKTI TERKINI DALAM DIAGNOSIS DAN PENGOBAT - Irsal Munandar; Irwandi Irwandi (Nusantara Hasana Journal, 2026)
Appendicitis is a common surgical condition in pediatric patients, with a higher prevalence in males, accounting for approximately 55–60% of cases. Although its exact etiology remains unclear, luminal obstruction caused by fecaliths, lymphoid hyperplasia, or parasitic infestation is frequently considered a contributing factor. The classic clinical presentation includes gradually worsening periumbilical abdominal pain that migrates to the right lower quadrant within 24 hours, accompanied by fever, anorexia, nausea, and vomiting. However, infants and young children may present with atypical symptoms, making diagnosis more challenging. Several clinical risk scoring systems have been developed to improve diagnostic accuracy by incorporating clinical symptoms, physical examination findings, and laboratory results. Ultrasonography is the recommended imaging modality due to its low cost and absence of radiation exposure, with reported sensitivity ranging from 72.5% to 94.8% and specificity from 95% to 99%, depending on operator experience. In preschool-aged children, acute appendicitis is associated with a higher risk of complications, including surgical site infections and intra-abdominal abscess formation. The risk of appendiceal perforation increases when diagnosis and treatment are delayed. Management includes fluid resuscitation, pain control, antibiotic therapy, and appendectomy. In cases of perforated appendicitis, percutaneous drainage may be required. Hospital readmission is most commonly related to infection, bowel obstruction, or persistent abdominal pain.